2016
DOI: 10.1002/cbic.201600339
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction of Shewanella oneidensis Extracellular Cytochromes by Organic Chromophores and Dye‐Sensitized TiO2

Abstract: The transfer of photoenergized electrons from extracellular photosensitizers across a bacterial cell envelope to drive intracellular chemical transformations represents an attractive way to harness nature's catalytic machinery for solar‐assisted chemical synthesis. In Shewanella oneidensis MR‐1 (MR‐1), trans‐outer‐membrane electron transfer is performed by the extracellular cytochromes MtrC and OmcA acting together with the outer‐membrane‐spanning porin⋅cytochrome complex (MtrAB). Here we demonstrate photoredu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…[ 88 ] Ainsworth and colleagues coated Ru II ‐dye‐sensitized TiO 2 nanoparticles with surface exposed MtrC and OmcA from S. oneidensis MR‐1 eliciting photocatalytic reduction of these proteins. [ 89 ] The inclusion of these cytochromes into abiotic Ru‐sensitized TiO 2 nanoparticles improved the ability of these nanoparticles to reduce protein complexes paving the way for the development of strategies that use surface‐exposed proteins for solar microbial synthesis.…”
Section: Nanoenzyme Tailoring and Synthesismentioning
confidence: 99%
“…[ 88 ] Ainsworth and colleagues coated Ru II ‐dye‐sensitized TiO 2 nanoparticles with surface exposed MtrC and OmcA from S. oneidensis MR‐1 eliciting photocatalytic reduction of these proteins. [ 89 ] The inclusion of these cytochromes into abiotic Ru‐sensitized TiO 2 nanoparticles improved the ability of these nanoparticles to reduce protein complexes paving the way for the development of strategies that use surface‐exposed proteins for solar microbial synthesis.…”
Section: Nanoenzyme Tailoring and Synthesismentioning
confidence: 99%
“…The transmembrane cytochrome MtrCAB, helped by OmcA located on the outside of the membrane, are known to transfer electrons between the interior of the cell and extracellular materials ( Figure 6) [231,232]. In the presence of a sacrificial electron donor, MtrC and OmcA can be photoreduced by water-soluble photosensitisers including eosin Y, fluorescein, proflavine, flavin, and adenine dinucleotide, riboflavin and flavin mononucleotide [233]. In an in vitro approach, it was showed that dye-sensitised TiO 2 nanoparticles can photoreduce MtrC or OmcA, either in solution or one an electrode surface [233][234][235] and it might be possible to extend this process to reductive photosynthesis in S. oneidensis [236].…”
Section: Whole-cell Based Semi-artificial Photosynthesismentioning
confidence: 99%
“…In the presence of a sacrificial electron donor, MtrC and OmcA can be photoreduced by water-soluble photosensitisers including eosin Y, fluorescein, proflavine, flavin, and adenine dinucleotide, riboflavin and flavin mononucleotide [233]. In an in vitro approach, it was showed that dye-sensitised TiO 2 nanoparticles can photoreduce MtrC or OmcA, either in solution or one an electrode surface [233][234][235] and it might be possible to extend this process to reductive photosynthesis in S. oneidensis [236]. To provide a proof-of-concept, we recently reconstituted MtrCAB into proteoliposomes encapsulating a redox dye, Reactive Red 120 (RR120), which can be reductively bleached.…”
Section: Whole-cell Based Semi-artificial Photosynthesismentioning
confidence: 99%
“…Electron transfer between a protein and inorganic material forms the foundation for a wide range of enzyme-and microbebased bioelectronic, 1 bioelectrocatalytic 2 and optobioelectronic 3 applications, including bioelectronic sensing, 1,4 solar production of fuels, 5 bioremediation, 6 biomining, 7 water purification, 8 and microbial 9 and enzymatic 10 fuel cells. The major scientific challenge in these fields is achieving electron transfer that is energetically efficient at a rate that is commensurate with enzyme turnover.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Electron transfer between a protein and inorganic material forms the foundation for a wide range of enzyme- and microbe-based bioelectronic, bioelectrocatalytic and optobioelectronic applications, including bioelectronic sensing, , solar production of fuels, bioremediation, biomining, water purification, and microbial and enzymatic fuel cells. The major scientific challenge in these fields is achieving electron transfer that is energetically efficient at a rate that is commensurate with enzyme turnover. ,, The coupling distance for direct electron transfer, which requires proper positioning of the redox site of the protein relative to the electrode material, varies between 10 and 30 Å. , To address this challenge, researchers have sought to orient enzymes on the electrode surface by displaying molecules on the electrode that mimic substrates of the enzyme, by attaching molecules that penetrate the enzyme close to an electron relay center on the electrode, , and electrostatically directed covalent bonding of the protein to the electrode .…”
Section: Introductionmentioning
confidence: 99%